Current collector for positive electrode of lithium-sulfur battery as well as preparation method and application of current collector
By using ion beam sputtering and cathode arc deposition techniques to form graphite-metal mixed layer and graphite layer in lithium sulfur batteries, the problem of poor bonding strength between current collector and active material is solved, significantly reducing the internal resistance of the battery and improving the stability of the battery and cycle life.
Patent Information
- Application Number
- CN202411235288.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-27
AI Technical Summary
The contact area between the metal current collector and the active material in the traditional lithium-sulfur battery electrode sheet is limited, resulting in an increase in the internal resistance of the battery, and the graphite carbon layer is difficult to control and has poor uniformity, affecting the stability of the battery.
Ion beam sputtering is used to inject carbon ions into the surface of the metal matrix to form a graphite-metal mixed layer, and a graphite layer is deposited on it through cathode arc deposition technology, using nitrogen as a gas ion source to improve the ionization rate and binding strength of the graphite target. A graphite-metal mixed layer with a thickness controlled between 90-110 nm and a graphite layer with a thickness of 1-2 μm were formed.
It effectively improves the contact area between the active material and the current collector, reduces the interface resistance, enhances the stability and cycle life of the battery structure, and improves the conductivity and adsorption of discharge products.
Smart Images

Figure CN119208614A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a current collector for a positive electrode of a lithium-sulfur battery, and a preparation method and application thereof. Background Art
[0002] In the traditional lithium-sulfur battery pole piece manufacturing process, the active material slurry is directly coated on the current collector surface, and after the slurry is dried, the active material is adhered to the current collector surface through a chemical binder. However, such a structural design has the problem of limited contact area between the metal current collector and the active material particles and large interface resistance, which in turn leads to an increase in the internal resistance of the battery, and has a negative impact on the battery performance, especially the performance under high current charging and discharging conditions. In addition, the bonding strength of the binder is limited. During the continuous charging and discharging process, it is easy for the active material and the current collector to expand and separate, resulting in further increase in the internal resistance of the battery, and even affecting the cycle life and safety performance of the battery. In addition, the traditional single-layer flat aluminum foil current collector has too small a contact area with the active material and cannot accommodate the phase transition and volume expansion and contraction of elemental sulfur during the charging and discharging process. Therefore, during the charging and discharging process of the battery, due to the large volume change, the active material may even fall off the surface of the aluminum foil substrate, reducing the battery life.
[0003] At present, the main method to solve the above problems is to increase the amount of binder in the slurry, chemically corrode or corona the surface of the current collector, or apply a coating containing a conductive material on the surface of the current collector, so as to increase the adhesion between the current collector and the active material. However, the first two methods also have serious defects in the above methods. The increase in the amount of binder will increase the internal resistance of the battery and reduce the energy density; chemical treatment and corona treatment will damage the surface of the current collector, reduce the strength of the foil, affect the subsequent battery processing performance, and have high production costs. At present, the most effective method is to coat a conductive layer on the surface of the current collector. The coating has the advantages of good conductivity, high specific surface area, and excellent bonding performance, and has better deformation ability than the metal current collector, which can increase the conductive contact between the active material and the current collector, reduce the interface internal resistance, and improve the bonding strength between the two. However, the existing conductive layer coated on the surface of aluminum foil is mainly prepared by a transfer coating process using a composite slurry mainly composed of conductive carbon and high-purity electronic aluminum foil as raw materials, but the carbon-coated aluminum foil prepared by this traditional process has many defects, and the thickness of the carbon layer is difficult to control and the uniformity is poor.
[0004] So far, there are related technologies to solve this problem. For example, Chinese patent CN110752377A discloses a battery current collector coated with a graphite-like film, a preparation method thereof, and a prepared pole piece. After pre-treating the surface of the metal foil current collector to remove surface impurities, the metal foil is cleaned by argon plasma sputtering, and then a graphite-like film is coated on the surface of the metal foil current collector by magnetron sputtering to solve the problem of poor bonding strength between the existing current collector and the active material on the current collector surface. However, the pole piece prepared by this technology is not for lithium-sulfur batteries, and the method for preparing the coated graphite-like film by this technology still has the technical problem that the graphite carbon layer is difficult to control and has poor uniformity, thereby resulting in poor battery stability. Summary of the invention
[0005] In view of this, the present invention provides a current collector for a lithium-sulfur battery, aiming to solve the problem in the prior art that the preparation of a graphite carbon layer is difficult to control and has poor uniformity, thereby resulting in poor battery stability.
[0006] In order to solve the above problems, the first aspect of the present invention provides a current collector for a lithium-sulfur battery positive electrode, comprising a metal substrate, carbon ions are implanted into the surface of the substrate by ion beam sputtering on at least one surface of the metal substrate to form a graphite-metal mixed layer, and then a cathode arc deposition technology is used to deposit a graphite layer on the graphite-metal mixed layer.
[0007] In the present invention, in order to improve the bonding force between the active material layer and the positive electrode current collector and the conductivity of the current collector, ion beam sputtering is used to perform surface injection deposition mixing on the metal substrate, and a gas ion source treatment is introduced during the entire ion beam graphitization process, which can effectively improve the ionization rate of the graphite target material during the ion beam graphitization process, increase the ion energy, facilitate the growth of ions on the surface of the substrate, reduce the surface difference between the substrate and the graphite layer, and further improve the bonding strength between the deposited graphite layer and the substrate. On this basis, cathode arc deposition technology is then used to deposit carbon on the graphite-metal mixed layer to form a graphite layer, and then the positive electrode current collector of the sulfur lithium ion battery is made, which can effectively increase the contact area with the active material particles, reduce the interface resistance, and improve the structural stability of the battery.
[0008] Furthermore, the metal substrate is aluminum foil.
[0009] A second aspect of the present invention provides a method for preparing the above-mentioned current collector for lithium-sulfur batteries, which is carried out in a vacuum chamber and comprises the following steps:
[0010] S1. Use argon plasma sputtering to clean the surface of the metal substrate, thereby cleaning the impurities and oxide film on the surface of the metal substrate
[0011] S2, using high vacuum ion beam sputtering, with graphite target as carbon source and nitrogen as gas ion source, injecting carbon ions onto the surface treated in step S1 to form a graphite-metal mixed layer;
[0012] S3. Using cathode arc deposition, with graphite target as carbon source and nitrogen as gas ion source, a graphite layer is deposited on the graphite-metal mixed layer to obtain the current collector for lithium-sulfur battery of the present invention.
[0013] In the preparation method of the current collector for lithium-sulfur battery provided by the present invention, nitrogen is introduced as a gas ion source during the entire ion beam graphitization process, which can effectively improve the ionization rate of the graphite target material during the ion beam graphitization process, increase the ion energy, further improve the bonding strength between the deposited graphite layer and the substrate, and thus improve the structural stability of the battery. Then, cathode arc deposition technology is used to deposit carbon on the graphite-metal mixed layer to form a graphite layer, and finally the positive electrode current collector of the sulfur-lithium battery is prepared, which can effectively increase the contact area with the active material particles, reduce the interface resistance, and thus reduce the internal resistance of the battery.
[0014] In addition, step S2 and step S3 of the preparation method of the present invention use inert gas nitrogen as the gas ion source, and introduce nitrogen doping during the ion beam graphitization process, which can effectively improve the conductivity of the matrix, and at the same time significantly improve the adsorption of the discharge product polysulfide, thereby improving the cycle stability of the battery.
[0015] Furthermore, the thickness of the graphite-metal mixed layer is 90-110 nm.
[0016] In the present invention, by maximizing the effect of high-energy ion source treatment, the thickness of the graphite-metal mixed layer is controlled to be 90-110nm. If the graphite-metal mixed layer is too thick, the transition effect cannot be achieved, which is equivalent to directly depositing carbon on the substrate, and the bonding performance is not good. If the graphite-metal mixed layer is too thin, the purpose of gradual transition cannot be achieved, which is not conducive to depositing a graphite layer on it.
[0017] Furthermore, in step S3 of the present invention, the thickness of the graphite layer is 1-2 μm. If the graphite layer is too thick, its conductivity is poor, and if the graphite layer is too thin, the interface bonding force is not strong.
[0018] Furthermore, in step S1, when the argon plasma sputtering is used to clean the surface of the metal substrate, the vacuum is drawn to 3.0×10 -3 Pa, the argon gas flow rate is 50 sccm, the sputtering power is 1-2 kW, and the sputtering cleaning time is 10-20 s.
[0019] Furthermore, when forming the graphite-metal mixed layer in step S2, the vacuum is evacuated to 3.0×10 -3Pa, high voltage is 4-8kV, negative pressure is 700-900V, arc voltage is 70-90V, and injection time is 1-2min.
[0020] In the present invention, during the process of forming the graphite-metal mixed layer in step S2, the ion beam carries a positive charge, and a negative pressure is provided in a vacuum, which can change the energy of the ion beam, thereby increasing the sp3 bond content therein, so that a small amount of diamond-like structure is doped in the graphite-metal mixed layer. The mixed structure of the two is beneficial to reducing the internal stress of the graphite layer, improving the strength of the membrane layer, and further improving the stability of the battery structure.
[0021] Furthermore, when forming the graphite layer in step S3, the pre-vacuum is pumped to 3.0×10 -3 Pa, arc current is 60-120A, negative pressure is 100-300V, deflection magnetic field current is 1.5-3A, and cathode arc deposition time is 10-20min.
[0022] In the present invention, a cathode arc is used to generate an ion beam, which has a high ionization rate and large ion energy, and is beneficial to the quality of the deposited film. By adjusting the conditions of cathode arc deposition, a graphite layer with a dense structure and high interface bonding strength is prepared.
[0023] A third aspect of the present invention provides a pole piece, which is formed by coating an anode slurry on the above-mentioned current collector for lithium-sulfur battery and then drying it.
[0024] A fourth aspect of the present invention provides a lithium-sulfur battery, wherein the pole piece used in the lithium-sulfur battery is the pole piece described above.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The positive electrode current collector for lithium-sulfur batteries provided by the present invention can effectively increase the contact area with active material particles, reduce interface resistance, and thus reduce the internal resistance of the battery.
[0027] (2) The present invention provides a current collector for the positive electrode of a lithium-sulfur battery, which effectively improves the steric hindrance of the material surface, can effectively accommodate the phase transition and volume expansion and contraction during the charge and discharge process, and improves the battery life.
[0028] (3) During the preparation process of the graphite-metal mixed layer of the present invention, the ion beam carries a positive charge, and the negative pressure provided in the vacuum can change the energy of the ion beam, thereby increasing the sp3 bond content therein, so that a small amount of diamond-like structure is doped in the graphite deposition layer. The mixed structure of the two is beneficial to reducing the stress in the graphite layer, improving the strength of the film layer, and further improving the structural stability of the battery.
[0029] (4) Compared with the existing method of coating a conductive layer on the surface of aluminum foil, the ion beam graphitization method of the present invention can effectively control the uniformity of the graphite layer. At the same time, the introduction of nitrogen as a gas ion source can effectively improve the conductivity of the positive electrode material and the adsorption of free sulfur, thereby improving the capacity and coulombic efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a cycle performance curve diagram of the battery using Example 1 and Comparative Example 1.
[0031] Figure 2 It is a graph of the AC impedance spectrum of Example 1 and Comparative Example 1 before and after 50 charge and discharge cycles. DETAILED DESCRIPTION
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the technical solutions of the present invention are described in detail with specific embodiments below. The test methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. In this embodiment, the metal substrate used is aluminum foil.
[0033] Example 1
[0034] This embodiment provides a method for preparing a current collector for a positive electrode of a lithium-sulfur battery, which is carried out in a vacuum chamber and includes the following steps:
[0035] S1. Place the aluminum foil in the vacuum equipment of the magnetron sputtering equipment and evacuate to 3.0×10 -3 Pa, argon plasma sputtering cleaning is performed to remove impurities on the aluminum foil, wherein the argon gas flow rate is 50 sccm, the sputtering power is 1 kW, and the sputtering cleaning time is 10 s.
[0036] S2, using high vacuum ion beam sputtering equipment, with graphite target as carbon source and nitrogen as gas ion source, the vacuum was pumped to 3.0×10 -3 Pa, carbon ions are injected into the surface treated in step S1 to form a graphite-metal mixed layer with a thickness of about 100 nm. The high vacuum ion beam sputtering equipment has a high voltage of 5 kV, a negative pressure of 800 V, an arc voltage of 80 V, and an injection time of 1 min.
[0037] S3, using cathode arc deposition equipment, with graphite target as carbon source and nitrogen as gas ion source, evacuated to 3.0×10 -3 Pa, deposited on the graphite-metal mixed layer to form a graphite layer with a thickness of about 1 μm, and the current collector for the lithium-sulfur battery of the present invention can be obtained. The arc current of the cathode arc deposition device is 100A, the negative pressure is 100V, the deflection magnetic field current is 2A, and the cathode arc deposition time is 10min.
[0038] Example 2
[0039] This embodiment provides a method for preparing a current collector for a positive electrode of a lithium-sulfur battery, which is carried out in a vacuum chamber and includes the following steps:
[0040] S1. Place the aluminum foil in the vacuum equipment of the magnetron sputtering equipment and evacuate to 3.0×10 -3 Pa, argon plasma sputtering cleaning is performed to remove impurities on the aluminum foil, wherein the argon gas flow rate is 50 sccm, the sputtering power is 1.5 KW, and the sputtering cleaning time is 15 s.
[0041] S2, using high vacuum ion beam sputtering equipment, with graphite target as carbon source and nitrogen as gas ion source, the vacuum was pumped to 3.0×10 -3 Pa, carbon ions are injected into the surface treated in step S1 to form a graphite-metal mixed layer with a thickness of about 90 nm. The high vacuum ion beam sputtering equipment has a high voltage of 6 kV, a negative pressure of 700 V, an arc voltage of 70 V, and an injection time of 1.5 min.
[0042] S3, using cathode arc deposition equipment, with graphite target as carbon source and nitrogen as gas ion source, evacuated to 3.0×10 -3 Pa, deposited on the graphite-metal mixed layer to form a graphite layer with a thickness of about 2 μm, and the current collector for the lithium-sulfur battery of the present invention can be obtained. The arc current of the cathode arc deposition device is 60A, the negative pressure is 100V, the deflection magnetic field current is 2A, and the cathode arc deposition time is 15min.
[0043] Example 3
[0044] This embodiment provides a method for preparing a current collector for a positive electrode of a lithium-sulfur battery, which is carried out in a vacuum chamber and includes the following steps:
[0045] S1. Place the aluminum foil in the vacuum equipment of the magnetron sputtering equipment and evacuate to 3.0×10 -3 Pa, argon plasma sputtering cleaning is performed to remove impurities on the aluminum foil. The argon gas flow rate is 50sccm, the sputtering power is 2kw, and the sputtering cleaning time is 20s.
[0046] S2, using high vacuum ion beam sputtering equipment, with graphite target as carbon source and nitrogen as gas ion source, the vacuum was pumped to 3.0×10 -3 Pa, carbon ions are injected into the surface treated in step S1 to form a graphite-metal mixed layer with a thickness of about 110 nm. The high vacuum ion beam sputtering equipment has a high voltage of 8 kV, a negative pressure of 900 V, an arc voltage of 90 V, and an injection time of 2 min.
[0047] S3, using cathode arc deposition equipment, with graphite target as carbon source and nitrogen as gas ion source, evacuated to 3.0×10 -3 Pa is deposited on the graphite-metal mixed layer to form a graphite layer with a thickness of about 2 μm, thereby obtaining the current collector for the lithium-sulfur battery of the present invention, wherein the arc current of the cathode arc deposition device is 120A, the negative pressure is 300V, the deflection magnetic field current is 3A, and the cathode arc deposition time is 20min.
[0048] Application Examples
[0049] Application Example 1
[0050] This application example provides a lithium-sulfur battery, and the preparation process is as follows.
[0051] Positive electrode preparation: A mixture of 70wt.% sublimed sulfur, 20wt.% carbon black and 10wt.% PVDF was mixed in NMP and ball-milled in a planetary ball mill at 16r / min for 24 hours to obtain a uniform slurry. The slurry was coated on the composite current collector prepared in Example 1 by an automatic coating machine using a scraper, dried in an oven at 5°C for 24 hours, and then punched into a disc with a diameter of 12mm to obtain a positive electrode sheet;
[0052] Negative electrode preparation: The negative electrode is a lithium sheet;
[0053] The dried positive electrode, PE / PP composite separator, and negative electrode were stacked in sequence, and then an electrolyte was added. The electrolyte was 1M LiTFSI as a lithium salt and a DOL / DME mixed solvent with a volume ratio of 1 was added to completely dissolve it, and then 0.2wt.% LiNO3 was added as an electrolyte additive to prepare a lithium-sulfur battery A1.
[0054] Application Comparative Example 1
[0055] The present application comparative example 1 provides a sulfur-lithium battery. Referring to application example 1, the difference from application example 1 is that the present application comparative example 1 uses commercially available positive electrode current collector aluminum foil to prepare a positive electrode sheet, and then prepares a lithium-sulfur battery B1.
[0056] Test results and comments
[0057] After testing, the internal resistance of battery A1 is 86Ω, and the internal resistance of battery B1 is 132Ω. The internal resistance of battery A1 is significantly reduced.
[0058] The electrochemical performance of batteries A1 and B1 was tested using a blue-electric test system and an electrochemical workstation. Figure 1 and 2 As shown, the A1 battery exhibits the highest initial discharge capacity of 843 mAh g at 0.2C. -1 After 350 cycles, the discharge capacity of A1 is 66 mAh g-1 , the capacity retention rate is 78.5%, and the B1 battery shows the highest initial discharge capacity of 655mAhg at 0.2C. -1 After 350 cycles, the discharge capacity of B1 is 343 mAh g -1 , the capacity retention rate is only 52.3%. It can be seen that the current collector prepared by the present invention can reduce the internal resistance of the battery and improve the capacity and coulombic efficiency of the battery.
[0059] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A current collector for a positive electrode of a lithium-sulfur battery, characterized in that: The invention comprises a metal substrate, wherein carbon ions are injected into the substrate surface by ion beam sputtering on at least one surface of the metal substrate to form a graphite-metal mixed layer, and then a graphite layer is deposited on the graphite-metal mixed layer by adopting cathode arc deposition technology.
2. The positive electrode current collector for lithium-sulfur batteries according to claim 1, characterized in that: The metal substrate is aluminum foil.
3. A method for preparing a current collector for a positive electrode of a lithium-sulfur battery according to any one of claims 1 to 2, characterized in that: It is carried out in a vacuum chamber and includes the following steps: S1, cleaning the surface of the metal substrate by argon plasma sputtering; S2, using high vacuum ion beam sputtering, with graphite target as carbon source and nitrogen as gas ion source, injecting carbon ions onto the surface treated in step S1 to form a graphite-metal mixed layer; S3. Utilize cathode arc deposition, use graphite target as carbon source, nitrogen as gas ion source, deposit to form graphite layer on graphite-metal mixed layer, and obtain current collector for lithium-sulfur battery.
4. The method for preparing a current collector for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: In the step S2, the thickness of the graphite-metal mixed layer is 90-110 nm.
5. The method for preparing a current collector for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: In the step S3, the thickness of the graphite layer is 1-2 μm.
6. The method for preparing a current collector for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: When the nitrogen plasma sputtering cleaning metal substrate surface in step S1 is carried out, the vacuum is evacuated to 3.0×10 -3 Pa, the argon gas flow rate is 50 sccm, the sputtering power is 1-2 kW, and the sputtering cleaning time is 10-20 s.
7. The method for preparing a current collector for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: When forming the graphite-metal mixed layer in step S2, the vacuum is pumped to 3.0×10 -3 Pa, high voltage is 4-8kV, negative pressure is 500-800V, arc voltage is 70-90V, and injection time is 1-2min.
8. The method for preparing a current collector for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: When forming the graphite layer in step S3, the vacuum is pumped to 3.0×10 -3 Pa, arc current is 60-120A, negative pressure is 100-300V, deflection magnetic field current is 1.5-3A, and cathode arc deposition time is 10-20min.
9. A pole piece, characterized in that: The pole piece is formed by coating the anode slurry on the current collector for lithium-sulfur battery according to any one of claims 1 to 2 and then drying it.
10. A lithium-sulfur battery, characterized in that: The pole piece used in the lithium-sulfur battery is the pole piece described in claim 9.